PENGARUH E-WOM, CUSTOMER RATING, DAN DISCOUNT PRODUCT TERHADAP IMPULSE BUYING PADA GENERASI Z DI KOTA SOLO - Lintang Sintya Nuraini; Aflit Nuryulia Praswati (Jurnal Manajemen Dirgantara, 2024)
The purpose of this study was to analyze the effect of e-wom, customer rating, and discount products on impulse buying in generation Z in Solo (case study of tiktok shop users). This research method is quantitative. The type of data used in this study is primary data. The data collection technique used in this research is through a questionnaire questionnaire. In this study, researchers will distribute questionnaires via google form to respondents. The population in this study is generation Z Tiktok users, both men and women in Solo City to find out their impulse buying behavior on the Tiktok application. The sampling technique used in this study uses non-probability sampling techniques, using the Incidental Sampling Method. The number of samples for this study were 120 respondents who are Tiktok Shop users in Solo City. The data analysis technique uses the SPSS program to simplify the calculation process. Data analysis techniques used to analyze data, namely validity test, reliability test, basic assumption test, classical assumption test, and hypothesis testing. The results of this study are that E-WOM has a significant effect on impulse buying. Customer rating has a positive effect on impulse. Discount product has a positive effect on impulse buying.